Fetal and adult progenitors give rise to unique populations of CD8(+) T cells - Wang, Jocelyn (Blood, 2016)
During the ontogeny of the mammalian immune system, distinct lineages of cells arise from fetal and adult hematopoietic stem cells (HSCs) during specific stages of development. However, in some cases, the same immune cell type is produced by both HSC populations, resulting in the generation of phenotypically similar cells with distinct origins and divergent functional properties. In this report, we demonstrate that neonatal CD8(+) T cells preferentially become short-lived effectors and adult CD8(+) T cells selectively form long-lived memory cells after infection because they are derived from distinct progenitor cells. Notably, we find that naïve neonatal CD8(+) T cells originate from a progenitor cell that is distinguished by expression of Lin28b. Remarkably, ectopic expression of Lin28b enables adult progenitors to give rise to CD8(+) T cells that are phenotypically and functionally analogous to those found in neonates. These findings suggest that neonatal and adult CD8(+) T cells belong to separate lineages of CD8(+) T cells, and potentially explain why it is challenging to elicit memory CD8(+) T cells in early life.